ISO 14000 (EMS) Awareness On Electronic Industries And Its Impact In International Market - Mohamad, Mazlan (2002)
This research is conducted to determine among electronic industries workers in Penang, selangor, Johor and Melaka. 52 electronic companies have been selected in the study. The research indicates that overall average, more than 80 percent of the respondents are fully aware of the ISo 14000 and its importance for implementation.